Recurrent severe hyperandrogenism during pregnancy: a case report. Issue 4 (24th March 2005) - Holt, H B; Medbak, S; Kirk, D; Guirgis, R; Hughes, I; Cummings, M H; Meeking, D R
Abstract : This report describes the case of a 28 year old woman with virilisation occurring in two successive pregnancies. Recurrent maternal virilisation is rare (seven previous reports) and this case is unique in its severity. Differential diagnoses include ovarian disease and fetal aromatase deficiency. New techniques to exclude a fetal cause were used in this case. This patient presented during the third trimester of her first pregnancy with rapid onset of hirsuitism, increased musculature, and deepening voice. A blood hormone profile revealed significant hyperandrogenism (testosterone, 72.4 nmol/litre; normal range, 0.5–3.0). She delivered a normal boy and maternal androgen concentrations returned rapidly to normal (testosterone, 0.8 nmol/litre). She presented two years later, during her second pregnancy, with similar symptoms and biochemistry (testosterone, 47.5 nmol/litre). Again, she delivered a healthy normal boy and androgens returned immediately to normal (serum testosterone, 2.0 nmol/litre). Ultrasonography revealed no evidence of ovarian (or adrenal) masses in either pregnancy. Umbilical cord venous blood sampling and placental assays revealed no evidence of fetal aromatase deficiency. Recurrent hyperandrogenism during pregnancy is rare. Ovarian luteoma rarely recurs and hyperreactio luteinalis does not lead to such pronounced androgen concentrations. Therefore, this patient has a unique ovarian condition that could be harmful to offspring and mother.